LAMA WAKTU PENGOMPOSAN SAMPAH MENGGUNAKAN METODE LEACHATE CIRCULATION DAN WINDROW - Kermelita, Deri; Yessy Sasmita, Ullya Rahmawati, (JURNAL MEDIA KESEHATAN, 2018)
Garbage are goods that are not used and disposed of by the owner of theprevious user. Waste management can be done with composting. Constraintssociety in the procces that takes a long time between 2-3 months. The purpose ofresearch is to compare the length of time waste composting using leachatecirculation and windrow. This type of research is experimentation with the designof post test with control. There are 12 sample, 2 treatment and 1 control. The firsttreatment using activator starbio with bioreactor leachate circulation and thesecond treatment using activator starbio with bioreactor windrow. The analysis ofresearch using univariate analysis and bivariate analysis with anova and LSD. Theresult stated that the establishment of a long time with activator starbio usingbioreactor leachate circulation is 10 days and the addition of compost activatorstarbio using bioreactor windrow is 7 days. Expected use of activator starbio withbioreactor leachate circulation and windrow on organic waste can be a solution,especially for people in overcoming the prolem of composting which takes a longtime to be faster.